2022
DOI: 10.1097/ogx.0000000000001074
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intrapartum Maternal Hemoglobin on Mode of Delivery and Short-Term Neonatal Outcome: A Systematic Review

Abstract: Importance: Maternal anemia in pregnancy is a common condition worldwide and is considered a risk factor for adverse neonatal and maternal outcome. Also high hemoglobin (Hb) levels are associated with adverse pregnancy outcomes. However, studies regarding the influence of intrapartum maternal Hb on mode of delivery and short-term neonatal outcome are limited and contradicting.Objective: The aim of this study was to provide an overview of current evidence regarding associations between intrapartum maternal Hb l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
0
0
Order By: Relevance
“…In terms of obstetrical factors, we observed that iron-deficiency anemic mothers had substantially more instrumental deliveries (all by vacuum) than non-iron-deficiency anemic mothers (4.3% vs. 0.8%), while the incidence of cesarean section was lower. This is a new finding as the previous systematic review showed that anemic women had a higher risk of cesarean [ 15 ]. However, the relation between gestational anemia and the mode of delivery remains unclear.…”
Section: Discussionmentioning
confidence: 81%
“…In terms of obstetrical factors, we observed that iron-deficiency anemic mothers had substantially more instrumental deliveries (all by vacuum) than non-iron-deficiency anemic mothers (4.3% vs. 0.8%), while the incidence of cesarean section was lower. This is a new finding as the previous systematic review showed that anemic women had a higher risk of cesarean [ 15 ]. However, the relation between gestational anemia and the mode of delivery remains unclear.…”
Section: Discussionmentioning
confidence: 81%